Toward understanding long-distance extracellular electron transport in an electroautotrophic microbial community. Issue 11 (17th October 2016) - Yates, Matthew D.; Eddie, Brian J.; Kotloski, Nicholas J.; Lebedev, Nikolai; Malanoski, Anthony P.; Lin, Baochuan; Strycharz-Glaven, Sarah M.; Tender, Leonard M.
Abstract : Here we show that long-distance extracellular electron transport occurs in a cathodic biofilm capable of CO2 fixation and O2 respiration. Abstract : Microbial electrosynthesis (ME) seeks to use electroautotrophy (the reduction of CO2 by microbial electrode catalysts) to generate useful multi-carbon compounds. It combines the utility of electrosynthesis with the durability of microorganisms and potential to engineer microbial metabolic processes. Central to achieving efficient ME is understanding the extracellular electron transport (EET) processes that enable certain microorganisms to utilize electrodes as metabolic electron donors. The Marinobacter-Chromatiaceae-Labrenzia (MCL) biocathode is an electroautotrophic biofilm-forming microbial community enriched from seawater that grows aerobically on gold or graphite cathodes, which we study to understand the mechanisms underpinning electroautotrophy. Evidence suggests that MCL reduces O2 using the cathode as its sole electron donor, directing a portion of the acquired electrons and energy to fix CO2 for biomass. A key feature of MCL is that it grows at +310 mV vs. SHE. Here, we apply electrochemical gating measurements, originally developed to study electron transport through polymer films, to study EET through living MCL biofilms. The results indicate that MCL biofilms employ a redox conduction mechanism to transport electrons across the biofilm/electrode interface and into the biofilm over multiple cell lengths (at least 5 μm) away from the electrode surface. In addition to making living MCL biofilms electrically conductive (60 μS cm −1 at 30 °C – more than 10 times greater conductivity than any other living microbial biofilm for which reliable measurements have been made), it enables electron uptake by cells not in direct contact with the electrode surface, which has not been previously reported for any biocathode. Confocal resonance Raman microscopy confirms the presence of c -type cytochromes as the putative redox cofactors involved in LD-EET, consistent with the activation energy for LD-EET obtained from the temperature dependency of the electrochemical gating measurements. These results provide the first report and mechanistic characterization of long-distance EET occurring within a multi-cell thick electroautotrophic biofilm – key milestones toward rational design and optimization of viable ME systems.